Teamwork as significant learning teaching strategy in teaching with popularizing their empowerment (2013)
ABSTRACT: "Purpose of research Show that the teacher should not only focus on the routine of teaching practices, and group work is essential in meaningful learning and also must also be based on the curriculum, in the texts, materials in teaching - learning, as these come to life and dynamism from the teacher is willing to promote the acquisition of knowledge and feedback in the classroom and to be responsible for their educational work becomes conscious of his duty and this will drive drive at school. Educational intervention was analyzed through teamwork and strategies were applied, dynamic, educational and meaningful to try to improve the teaching of geography in terms of 2nd grade students of secondary, making use of group work."